1999
DOI: 10.1002/cbm.304
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine treatment of long‐standing schizophrenia and serious violence: a two‐year follow‐up study of the first 50 patients treated with clozapine in Rampton high security hospital

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Certain positive experiences corresponded to the clinical evidence for specific interventions, for example, the value of medication (specifically Clozapine) in managing symptoms or the benefits reported from talking therapies (Dalal, Larkin, Leese, & Taylor, 1999). Accounts of experiences also provide original insights into elements of care, which can be substantiated by a degree of theoretical coherence.…”
Section: Discussionmentioning
confidence: 85%
“…Certain positive experiences corresponded to the clinical evidence for specific interventions, for example, the value of medication (specifically Clozapine) in managing symptoms or the benefits reported from talking therapies (Dalal, Larkin, Leese, & Taylor, 1999). Accounts of experiences also provide original insights into elements of care, which can be substantiated by a degree of theoretical coherence.…”
Section: Discussionmentioning
confidence: 85%
“…There is evidence for pharmacological interventions, with reports of benefits from the use of Clozapine with patients who have treatment resistant schizophrenia (Dalal et al, 1999;Swinton & Haddock, 2000;Tiihonen et al, 2003); findings that are congruent with existing UK practice guidance (National Institute for Clinical Excellence, 2009). Preliminary evidence for psychoeducation for those with mental illness (including schizophrenia) indicates improvements in insight and therapy engagement, emphasizing the interaction effects of interventions in the high secure setting (Aho-Mustonen et al, 2008).…”
Section: Discussionmentioning
confidence: 86%
“…Two studies (Dalal, Larkin, Leese, & Taylor, 1999;Swinton & Haddock, 2000) investigating the efficacy of Clozapine compared to a non-Clozapine group reported modest improvements in discharge rates at two years respectively (SMD = 0.58; RR = 2.45). A further follow up at 4 years was reported for the former study (RR = 1.96) in addition to positive reductions in violent behaviour (RR = 1.24).…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…In Chiles et al, 87 for example, all the improvement apparently occurred between weeks 2 and 4 of treatment. In Dalal et al 94 the reduction in violence occurred only in the early phase. One might tentatively conclude that, while the anti-aggressive benefit may not emerge immediately, an empirical trial of perhaps one month should be sufficient to gauge the likelihood of response to an antipsychotic medication.…”
Section: Discussionmentioning
confidence: 96%
“…Bitter et al, The investigation reportedly began with 7655 subjects, of whom 5018 received monotherapy, of whom 3135 completed. This report seems to be a post hoc analysis of a prospective study, but the method, as reported, is ambiguous Buckley, et al, 1995 andDalal et al, 1999. are also reported inTable 3because subsets of patients were preselected as violent.Although Chiles et al, 1994 is a retrospective study, data were only reported for the subset that had completed 12 weeks of tx, so that the completion rate is only 82.7%.Re.Swanson et al, 2004b: This paper included data on 124 completers but fails to report how many of the 403. patients were on one of the two study drugs at the start of the study period.Re Wilson, 1992…”
mentioning
confidence: 79%